Chemical Composition and The Potential Biological Activities of Piper Betel – A Review - Salwani, Ismail; Mohd Adzim Khalili, Rohin; Mohd Nizam, Zahary (2018)
Piper betel is a member of the family Piperaceae, commonly known as Sirih (Malaysia and Indonesia), Paan (India and Bangladesh), Betel (English) and Phlu (Thailand). It is widely found and grown in India, Sri Lanka, Malaysia, Indonesia, Philippines, other Southeast Asian and East African countries. Piper betel is widely used throughout the world even in modern days due to its known medicinal properties. Betel plant contains various biologically active compounds, which are responsible for its numerous pharmacological actions. The therapeutic profile reveals Piper betel to have a high potential for treating many diseases and conditions such as chronic renal disease, atherosclerosis, and diabetes mellitus. Further studies of betel plant are recommended to focus on the variety of metabolic activities in human, thus, improving its usage medically that will be beneficial to humanity.